Postpartum Sterilization Choices Made by HIV-Infected Women. Issue 4 (2005) - Stuart, Gretchen S.; Castaño, Paula M.; Sheffield, Jeanne S.; McElwee, Barbara; McIntire, Donald D.; Wendel, George D.
Abstract : Objective. To assess if HIV-infected women made different choices for postpartum sterilization after implementation of the Pediatric AIDS Clinical Trials Group protocol 076 (November 1, 1994) compared to before implementation. Study design. A retrospective cohort study in which medical records were reviewed to obtain demographic, obstetric and HIV-related data from January 1993 through December 2002. HIV-infected women who completed a pregnancy by birth or abortion were divided into two comparison groups: "Pre-076" and "Post-076". The primary outcome was sterilization by postpartum tubal ligation. Results. Forty-two women (74%) in the Pre-076 group chose sterilization compared to 139 of 310 women (45%) in the Post-076 group (unadjusted OR 3.44, 95 % CI 1.83, 6.47). Seventy-one percent of women younger than 21 years of age in the Pre-076 Group chose sterilization compared with only 35% of women younger than 21 years in the Post-076 group ( p =0.0136). Similarly, 78% of primiparous women chose sterilization after their first pregnancy in the Pre-076 group, compared to 14% in the Post-076 group ( p < 0.001). Conclusions. Since the implementation of PACTG 076 protocol in November 1994, fewer HIV-infected women chose postpartum sterilization. The typical woman who now chooses postpartum sterilization is less likely to be young or primiparous than those who chose sterilization before PACTG Protocol 076 implementation.